Bioactive Compound, Antioxidant, and Radical Scavenging Activity of Some Plant Aqueous Extracts for Enhancing Shelf Life of Cold-Stored Rabbit Meat - Huda Abdalrahman Al Jumayi; Ayman Younes Allam; Alaa El-D; Eman Hassan Algarni; Samy F. Mahmoud; Amin Abd El Halim Kandil (MDPI AG, 2022)
The potential radical scavenging, antioxidant activities (DPPH and ABTS) and bioactive constituents of several plant aqueous extracts (Curcuma longa, CL; Myristica fragrans, MF; Zingiber officinale, ZO; Cymbopogon citratus, CC and Thymus vulgaris, TV as well as their mixture) were investigated. The effect of these extracts on quality aspects (sensory characteristic, color traits, and Thiobarbituric acid) of rabbit meat during a 16-day cold (4 ± 2 °C) storage were investigated. Total phenolics and flavonoid contents of all extracts ranged from 13.27 ± 0.57 to 25.23 ± 0.49 mg GAE/g and 6.57 ± 0.22 to 13.24 ± 0.19 mg quercetin/g, respectively. The aqueous extract of MF had the highest (p ≤ 0.05) ABTS scavenging activity (4.55 μ mol Te/g dry extract), whereas the highest (p < 0.05) DPPH scavenging activity was detected in ZO extract (9.32 μ mol Te/g dry extract). Identification of extracts' bioactive compounds by GC-MS revealed that Eugenol (34.51%), Cinnamaldehyde (44.71%), Carvacrol (40.49%), Eicosane aldehyde (31.73%), and thymol (50.04%) are the first abundant bioactive compounds of CL, MF, ZO, CC, and TV aqueous extracts, respectively. Generally, the thiobarbituric acid reactive substances (TBARS) of all cold stored rabbit meat increased (p < 0.05) by increasing the storage time. The lowest TBARS values were detected for the samples treated with 0.2% of plant extracts mixture, which increased the shelf life of cold-stored rabbits by 50%. Significant (p < 0.05) increases in both L* and b* were observed with extended storage time. Meanwhile, the redness of the cold stored rabbit meat had an opposite trend. Treating the cold stored rabbit meat with 0.2% of the extract's mixture doubled the storage time with acceptable odor and taste. The results indicated that the studied plant extracts may be effective against rancidity and may be used as a natural antioxidant to prolong the shelf life of cold-stored rabbit meat.